SOVIET LEGASY: THE CONSTRUCTION OF THE KEMPIR-ABAD OF RESERVOIR AND ITS SOCIAL CONSEQUENCES IN THE KYRGYZ SSR (1962-1973) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article offers a comprehensive analysis of the construction of the Kempir-Abad (Kampyr-Ravat) reservoir from 1962 to 1973, viewing it as a prime example of Soviet “nature engineering” policy and hydro-imperialism. Based on a synthesis of archival documents, ethnographic field research, and oral testimonies from over 80 witnesses from the villages of Kyimyl, Ana-Kyzyl, Kyzyl-Oktyabr, Alga, Kashka-Terek (Aigyr-Zhal), and Karool in the Uzgen District, we examine the mechanisms of forced resettlement, the profound economic losses, cultural trauma, and adaptive strategies of local communities in the Kyrgyz SSR.Particular attention is given to the asymmetry in inter-republican relations, the inequitable compensation, and the role of kinship networks in maintaining social resilience during systemic upheaval. The findings of the study underscore the deep human cost of Soviet modernization in Central Asia.
Keywords: Kempir-Abad, hydro-imperialism, forced resettlement, political ecology, collective memory, community resilience, Kyrgyz SSR.